Evaluation of the point of care Afinion AS100 analyser in a community setting. (May 2017) - Jain, Anjly; Rao, Nandini; Sharifi, Mahtab; Bhatt, Nirav; Patel, Payal; Nirmal, Divyabala; Persaud, Jham Want; Nair, Devaki R
Background: A 'one stop shop' model for multifactorial risk factor management in a culturally sensitive environment may improve cardiovascular disease and diabetes prevention. A full biochemical profile for cardiovascular disease risk assessment includes a lipid profile, glucose, glycated haemoglobin and urine albumin creatinine ratio measurements. This may require the use of more than one point of care testing instrument. Methods: Individuals who attended a community cardiovascular disease risk screening or an audit programme of the diabetic care pathway in the community were sampled. Bland–Altman and Deming regression plots were used to assess agreement between methods for total cholesterol, high-density lipoprotein cholesterol, triglycerides, glycated haemoglobin and urine albumin creatinine ratio. Results: There was good agreement between the Afinion AS100 analyser, Cholestech LDX and the laboratory methods for total cholesterol, high-density lipoprotein cholesterol and triglycerides ( n  = 232). The Afinion AS100 agreed well with the laboratory method for glycated haemoglobin ( n  = 255) and urine albumin creatinine ratio ( n  = 176). There was statistically significant bias ( p  = 0.03 to <0.0001) for several measurements. However, these were judged not to be clinically relevant. Specifically for the total cholesterol and high-density lipoprotein cholesterol values, we obtained good agreement (weighted kappa: 0.91 and 0.94 for the Afinion AS100 vs. Cholestech LDX and Afinion AS100 vs. laboratory method, respectively) for cardiovascular disease risk calculation using QRISK2. Conclusions: Point of care testing can support a 'one stop shop' approach by providing rapid, reliable results. The Afinion AS100 analyser provides a multi-analyte platform and compares well with laboratory-based methods and another well-established point of care testing analyser.